Policies of Social Action and Inclusion and Current Brazilian Tensions - Maura Corcini Lopes; Alfredo Veiga-Neto (Universidade de Lisboa, 2016)
By briefly describing the events that highlight the emergence of policies of social action and inclusion in Brazil, from the 1930's through the mid- 2010's, this paper presents reflections about the production of a new type of individual who possesses, in the learning processes, the potency to invert the relationship between absolute poverty exclusion for the lack of competence- in/exclusion. Such policies, as they operate as State strategies for the biopolitical government of the population, produce in articulation with other practices what may be considered a subspecies of the Homo oeconomicus, namely, the Homo oeconomicus discentis accessibilis. The digital inclusion is discussed as an important and effective operator for inclusion in Brazil.